Performance Level of Pencak Silat T Kick Skills Tapak Suci Putera College of Muhammadiyah Branch Makassar 02 - Hasbi Asyhari; Nurliani Nurliani (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. This research focuses on evaluating the proficiency of pencak silat T kick techniques among the students of Tapak Suci Putera College, Muhammadiyah branch Makassar 02. The study aims to provide a comprehensive analysis of the level of performance achieved by the students in executing these skills, taking into account various technical nuances and factors that affect the outcome. The results of this study will be useful for both instructors and students in improving the quality of training and enhancing their overall performance in this martial art. Materials and methods. The research conducted was survey-based descriptive research, aimed at studying 15 active male martial artists. The sample was selected using purposive sampling, which is a non-random sampling technique where the researcher selects participants based on specific characteristics relevant to the study. Results. The study evaluated the T-kick performance of collegiate athletes at Tapak Suci branch Makassar 02 using their right and left feet. The results showed that using the right foot, 53% of the athletes demonstrated good skill, 27% had fair skill, 20% had less skill, and none of the athletes had very good or very less skill. Similarly, using the left foot, 47% of the athletes demonstrated good skill, 20% had enough skill, 33% had less skill, and none of the athletes had very good or very less skill. Conclusion. Based on the research findings, it can be inferred that the athletes from Tapak Suci Putera Muhammadiyah Branch Makassar 02 exhibited commendable performance in executing the T-kick technique of pencak silat, irrespective of their dominant foot (right or left). The level of performance was classified as 'Good'.